Analisis Tingkat Kesehatan Koperasi Pada Koperasi Simpan Pinjam âCendrawasihâ Kecamatan Gubug Tahun Buku 2011 - Munir, Misbachul; Indarti, Iin (Jurnal Kajian Akuntansi dan Bisnis, 2012)
Koperasi Simpan Pinjam Cendrawasih Gubug was rising the membersand their SHU from year to year untill 2010. It needs an evaluation to detect how actuallythe level of that cooperation. This research method used descriptive analysis. TheResearcher didnt used population and example because it was reseach study case . Toknow the health level at level at Koperasi Simpan Pinjam Cendrawasih at 2011 groundedon KEP MEN20/per/M.KUKM/XI/2008. The health score of this cooperationCendrawasih at 2011 was health enough , it was showed from from health scoregrounded to 7 aspect is Capital aspect get 15 point, aspect of activa productive is 20point, The aspect of management is 8,7 point, the aspect of eficiency ir 8.5 point, aspectof independence and development is 3,75 point, then aspect of identity cooperation is 3point. The entire of total score is 60,2. Grounded to category ( 60-80 )Keywords: aspect of capital, aspect of productif, aspect of management, aspect of liquidity